Didactic strategy of linear algebra with collaborative learning in mathematics pedagogical training - Díaz, Verónica; Hernández-Díaz, Alejandro; Oval, Carmen (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
This article details the design and implementation of a didactic intervention strategy aimed at enhancing the pedagogical skills of mathematics education students in the teaching of linear algebra. Given the challenges students often face in grasping abstract mathematical concepts, the intervention leverages the Anthropological Theory of Didactics and Collaborative Learning as its theoretical framework. The phases of the intervention's execution in the classroom, along with the key elements for successful implementation, are thoroughly outlined. The results indicate significant improvements in academic performance in the units’ covering determinants, matrices, and systems of linear equations, while challenges persist in the unit on vector spaces. In terms of task genres, students showed proficiency in defining and calculating, although there was a lower level of mastery in demonstrating. The study concludes that, despite a general unfamiliarity with autonomous learning, the future educators were able to become active and effective contributors to their own mathematical knowledge construction through collaborative group work.